2017
DOI: 10.21037/jtd.2017.06.66
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in imaging of peripheral pulmonary arteries

Abstract: Background: To establish an optical coherence tomography (OCT)-based method for imaging peripheral pulmonary arteries. Methods:We recruited eight patients (five men; average age, 48±12 years; peripheral pulmonary artery thrombosis, three patients; idiopathic pulmonary hypertension, three patients; interstitial lung disease, and September 2010. OCT was performed using both the conventional OCT imaging method (COI) and the improved pulmonary artery imaging method (IPI). In the IPI, contrast agent was used as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In patients with PH, Jiang et al even showed a positive predictive value of 91% for a WT of ≥0.176 mm, underlining the potential of OCT as an additional diagnostic parameter in PH patients ( 20 ). However, to our best knowledge, no standardised settings for the operational procedure ( 21 ) and image analysis procedure of pulmonary arterial OCT have been determined. Comparison of absolute values for measured WT of the PA deviates ( 18 , 20 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with PH, Jiang et al even showed a positive predictive value of 91% for a WT of ≥0.176 mm, underlining the potential of OCT as an additional diagnostic parameter in PH patients ( 20 ). However, to our best knowledge, no standardised settings for the operational procedure ( 21 ) and image analysis procedure of pulmonary arterial OCT have been determined. Comparison of absolute values for measured WT of the PA deviates ( 18 , 20 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the penetration depth of OCT in the PA is 2–3 mm which limits a detailed presentation of the strongly thickened pulmonary arterial walls ( 11 , 37 ). However, in this study, a minimum of one OCT record per patient had sufficient quality, although insufficient image quality is a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation